Simulasi Pergerakan Dana Tabarru Produk Asuransi Jiwa Unit Link Syariah - Indah Gumala Andirasdini; Ratih Suryaningsih (Indonesian Journal of Applied Mathematics, 2023)
Premi or known as Contributions in sharia insurance are part of tabbaru fund which is paid by participants. Tabarru’ has puposes to provide the "benevolent funds" with the sincere intention of helping each other among fellow "takaful" participants when one of them suffers a misfortune, such as death. These funds provided by insurance participants will be used to pay claims or insurance benefits by insurance companies. A sharia insurance company is considered doing well financially when tabbaru's funds are well managed to paid the insurance claim. In addition, the company must have sufficient funds to overcome the underwriting deficit in case it happen. This study aims to simulate the adequacy of a company's tabarru’ funds in each period, assuming there is no change in the number of participants during that period. The simulation results can conclude the adequacy of tabarru funds to pay participant claims. Sum of tabarru’ funds are calculated based on the sum of each participant's tabarru’ contribution, which is affected by each sharia-linked unit life insurance product and the participant's policy period. The tabarru’ fund sufficiency simulation is predicted using the IMA(2,1) time series model. The results of this study conclude that the average tabarru funds for each product will be used up in the following year with the criteria of the number of people making claims of not less than five participants. In this study, we found that the company can survive if the number of claims paid from the tabarru' fund with participants tabarru' fund contributions is balanced.